Perancangan Sistem Absensi Berbasis Website dengan Metode Waterfall di BAPPEDA Kebumen - Irfan, Muhammad; Rosid, Moch. Abdul Ghonny Nur; Lutfiyani, Anisa (Jurnal Kridatama Sains dan Teknologi, 2023)
Abstrak Sistem absensi yang terdapat pada suatu instansi umumhe attendance system in an agency generally still uses manual methods. Manual attendance systems are still applied in various regions, especially civil servants in Kebumen Regency. For this reason, an online and web-based attendance system is needed. the purpose of this research is to maximize and produce quality employee attendance so that it is safer and protected by the system and more effective and efficient. And in conducting this research, researchers used waterfall methodology. The research method used in creating an employee attendance system, the author uses the waterfall method by having five design stages, namely Analysis, Design, Testing, Implementation and Evaluation. Designing a Website-Based Attendance System with the Waterfall Method at BAPPEDA Kebumen, namely the existence of this web-based attendance system will make it easier for employees to report attendance easily, quickly and on time according to the work schedule taken, and can increase efficiency and effectiveness in data processing quickly and of course accurately in the work environment at BAPPEDA Kebumen. It is hoped that for further software system development research whose purpose is to expand the scope of the system, so that it no longer focuses on attendance and daily reports, but can cover all parts of the employee performance process that occurs at BAPPEDA Kebumen and the need for system updates at certain times whose purpose is to increase the effectiveness and efficiency of the system.Keywords: Attendance, Website, Waterfallnya masih menggunakan cara manual. Sistem absensi manual masih diterapkan di berbagai daerah khususnya pegawai sipil dikabupaten Kebumen. Untuk itu dibutuhkan suatu sistem absensi yang berbasis online dan web. tujuan dari penelitian ini adalah untuk memaksimalkan dan menghasilkan kualitas absensi pegawai supaya lebih aman dan terproteksi oleh sistem serta lebih efektif dan efisien. Dan dalam melakukan penelitian ini, peneliti menggunakan metedologi waterfall. Metode penelitian yang digunakan dalam membuat sistem absensi pegawai, penulis mengunakan metode waterfall dengan memiliki lima tahap perancangan yaitu Analisis, Rancangan, Pengujian, Implementasi dan Evaluasi. Perancangan Sistem Absensi Berbasis Website Dengan Metode Waterfall Di BAPPEDA Kebumen yaitu dengan adanya sistem absensi yang sudah berbasis web ini akan memudahkan pegawai untuk melaporkan absensi dengan mudah, cepat serta tepat waktu dengan sesuai jadwal kerja yang diambil, serta dapat meningkatkan efeseiensi serta efektifitas dalam pengolahan data dengan cepat dan tentunya akurat di lingkungan kerja di BAPPEDA Kebumen.Diharapkan untuk penelitian pengembangan sistem perangkat lunak selanjutnya yang tujuan nya untuk memperluas cakupan sistem, sehingga tidak lagi berfokus pada absensi dan laporan harian, tetapi dapat mencakup semua bagian dari proses kinerja pegawai yang terjadi di BAPPEDA Kebumen dan kebutuhan akan pembaruan sistem pada waktu tertentu yang tujuan nya untuk meningkatkan efektivitas dan efisiensi sistem. Kata kunci: Absensi, Website, Waterfall Abstract The attendance system in an agency generally still uses manual methods. Manual attendance systems are still applied in various regions, especially civil servants in Kebumen Regency. For this reason, an online and web-based attendance system is needed. the purpose of this research is to maximize and produce quality employee attendance so that it is safer and protected by the system and more effective and efficient. And in conducting this research, researchers used waterfall methodology. The research method used in creating an employee attendance system, the author uses the waterfall method by having five design stages, namely Analysis, Design, Testing, Implementation and Evaluation. Designing a Website-Based Attendance System with the Waterfall Method at BAPPEDA Kebumen, namely the existence of this web-based attendance system will make it easier for employees to report attendance easily, quickly and on time according to the work schedule taken, and can increase efficiency and effectiveness in data processing quickly and of course accurately in the work environment at BAPPEDA Kebumen. It is hoped that for further software system development research whose purpose is to expand the scope of the system, so that it no longer focuses on attendance and daily reports, but can cover all parts of the employee performance process that occurs at BAPPEDA Kebumen and the need for system updates at certain times whose purpose is to increase the effectiveness and efficiency of the system. Keywords: Attendance, Website, Waterfall